PENERAPAN TERAPI REBUSAN AIR DAUN BINAHONG UNTUK MEMPERCEPAT PENYEMBUHAN LUKA PERINEUM PADA IBU POST PARTUM DI RUANG CILAMAYA BARU RSUD KARAWANG - Yuli Erlina,; Dina, Dina; Rendi Fauzi, (Journal of Innovation Research and Knowledge, 2024)
Background: Perineal wounds are a common complication experienced by postpartum mothers due to childbirth. Suboptimal wound care can lead to infection and slow the healing process. One alternative therapy that can be used to accelerate wound healing is a decoction of binahong leaves (Anredera cordifolia), which contains saponins, flavonoids, and polyphenols that play a role in tissue regeneration and anti-inflammatory effects. Objective: This study aimed to determine the effect of binahong leaf decoction therapy on accelerating perineal wound healing in postpartum mothers in the Cilamaya Baru Ward at Karawang Regional Hospital. Methods : This study used a pre-experimental design with a One Group Pretest-Posttest Design approach. The population was all postpartum mothers with perineal wounds in the Cilamaya Baru Ward at Karawang Regional Hospital. A sample of 16 respondents was selected using purposive sampling. The binahong leaf decoction therapy was administered twice daily for three days. The data collection instrument used the REEDA scale (Redness, Edema, Ecchymosis, Discharge, Approximation) observation sheet. Data analysis was performed using the Wilcoxon Signed Rank Test with a significance level of 0.05. Results: The average REEDA score before therapy was 6.25 and after therapy was 2.18. The Wilcoxon test showed a p-value of 0.001 (p < 0.05), indicating a significant difference between before and after administration of binahong leaf decoction therapy. Conclusion: Binahong leaf decoction therapy is effective in accelerating perineal wound healing in postpartum mothers in the Cilamaya Baru Ward of Karawang Regional Hospital